The effect of mobile banking on the performance of commercial banks in Nigeria - Bagudu, Hauwa Daniyan; Mohd Khan, Shazida Jan; Roslan, Abdul-Hakim (IJCU Publishing, California South University, 2017)
Today, commercial banks are confronted with challenges that range from debt crises to the tight competition in the market. Customers’ impatience has increased considerably as they are more knowledgeable than before. Thus, the introduction of mobile services in the banking industry has added to the challenges facing commercial banks as they have to embrace the new technology or lose business. Mobile banking in Nigeria has completely transformed the banking industry and any commercial bank operating in Nigeria can only ignore that fact at its own risk. This study, therefore, aims to investigate the mobile banking effects on Commercial Banks financial performance in Nigeria. Simple random techniques were employed in this study in selecting 22 commercial banks. To facilitate the obtaining of relevant data that was used for analysis in this study, structured questionnaire was used. Descriptive statistics involving simple graphical charts was applied in presentation and analysis of data. The study, therefore, concludes that mobile banking positively and significantly affects the financial performance of commercial banks in Nigeria. The study recommends that commercial banks should keep adopting and using mobile banking in their operations because the number of people with access to a mobile handset is increasing every day.